The impact of Stock index futures on the Turkish spot market - ÇAĞLAYAN AKAY, EBRU (My University, 2011)
The aim of this work is to investigate the impact of the introduction of index futures on the volatility of the underlying Turkish spot market. For this purpose, symmetric and asymmetric conditional-volatility models have been employed by using the Istanbul Stock Exchange 30 Index (ISE30) daily returns. The evidences indicate that there have been significant changes in the structure of volatility in the ISE30 spot market, following the onset of futures trading. It has also been found that the asymmetric effect is relevant in the post-futures period.
Keywords: futures; GARCH; index; Volatility